ANALISIS PENGARUH UPAH MINIMUM, JUMLAH INDUSTRI, DAN INFLASI TERHADAP KESEMPATAN KERJA DI KOTA/KABUPATEN JAWA BARAT - Aziziah, Alvina; Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research focuses on the impact of minimum wages, number of industries, and inflation to job vacancy in the City/Regency of West Java 2017-2021. This study is important to research because job opportunities in West Java are still relatively low as evidenced by the high number of unemployement and job seekers. Whereas, West Java is known as central industry area which should be able to absorb labor and open up job opportunities in West Java. The purpose of this study is to find and analyze the influence of the minimum wage, the number of small and medium industries, the number of large industries and inflation to job opportunities. The data analysis method used in this study is panel data regression analysis. The results of the study show the minimum wage, the number of small and medium industries, and the number of large industries partially have a positive and significant effect on job opportunities. Meanwhile, Inflation has no effect on job opportunity. Then simultaneously the minimum wage, the number of small and medium industries, the number of large industries, and inflation have a significant effect on job opportunity.